2020
DOI: 10.1103/physrevb.102.214101
|View full text |Cite
|
Sign up to set email alerts
|

Nonlinear and hysteretic ultrasound propagation in solid He4 : Dynamics of dislocation lines and pinning impurities

Abstract: We report on the measurements of 9.6 MHz ultrasound propagation down to 15 mK in polycrystalline quantum solid 4 He containing 0.3 and 20 ppm 3 He impurities. The attenuation and speed of ultrasound are strongly affected by the dislocation vibration. The observed increase in attenuation from 1.2 K to a peak near 0.3 K is independent of drive amplitude and reflects crossover from overdamped to underdamped oscillation of dislocations pinned at network nodes. Below 0.3 K, amplitude-dependent and hysteretic variat… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
8
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 36 publications
0
8
0
Order By: Relevance
“…More recently the "anomalous" absorption peak at T = 0.7K peak has also been found in Ref. [27]. The origin of such a peak is unknown.…”
mentioning
confidence: 71%
See 2 more Smart Citations
“…More recently the "anomalous" absorption peak at T = 0.7K peak has also been found in Ref. [27]. The origin of such a peak is unknown.…”
mentioning
confidence: 71%
“…[26]). More recent studies using ultrasound have reported smaller values-ranging from 0.18K to 0.35K [27] for the 3 He binding energy. There are also reports of the activation behavior of the intrinsic origin -unrelated to 3 He impurities.…”
mentioning
confidence: 90%
See 1 more Smart Citation
“…This noninvasive method allows to characterize the distribution of dislocation lengths as was done for polycrystals [1,50,82] and single crystals [2]. As far as we are aware, it was so far only possible to apply it to solid helium-thanks to the short relaxation time of 3 He impurities [48] and high mobility of dislocations.…”
Section: Hysteretic Amplitude Dependence At Moderate Strainmentioning
confidence: 99%
“…The response of hcp 4 He , with various 3 He concentrations, to an AC shear stress has been investigated previously by a range of techniques at different frequencies: shear in a torsional oscillator (TO) (200 Hz-2 kHz) [39], transverse sound (1 Hz-100 kHz) [2,16,[40][41][42][43][44][45][46] and ultrasound [47][48][49][50] , scattering of thermal phonons (8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24) [4,[51][52][53][54][55][56]. Most can be explained in terms of interaction with vibrating dislocations [39,49].…”
Section: Introductionmentioning
confidence: 99%